2018
DOI: 10.1016/j.redox.2017.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Chicoric acid prevents PDGF-BB-induced VSMC dedifferentiation, proliferation and migration by suppressing ROS/NFκB/mTOR/P70S6K signaling cascade

Abstract: Phenotypic switch of vascular smooth muscle cells (VSMCs) is characterized by increased expressions of VSMC synthetic markers and decreased levels of VSMC contractile markers, which is an important step for VSMC proliferation and migration during the development and progression of cardiovascular diseases including atherosclerosis. Chicoric acid (CA) is identified to exert powerful cardiovascular protective effects. However, little is known about the effects of CA on VSMC biology. Herein, in cultured VSMCs, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
121
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(132 citation statements)
references
References 67 publications
(101 reference statements)
3
121
0
Order By: Relevance
“…Precious studies showed that ROS generation was associated with the proliferation of cancer cells. [18][19][20] To determine whether KRT17 affects ROS activation, we used DCFH-DA to detect intracellular ROS. As shown in Figure 4, after transfection with siKRT17 for 1 and 24 h, ROS activation increased over time.…”
Section: Downregulation Of Krt17 Suppressed Ros Activationmentioning
confidence: 99%
“…Precious studies showed that ROS generation was associated with the proliferation of cancer cells. [18][19][20] To determine whether KRT17 affects ROS activation, we used DCFH-DA to detect intracellular ROS. As shown in Figure 4, after transfection with siKRT17 for 1 and 24 h, ROS activation increased over time.…”
Section: Downregulation Of Krt17 Suppressed Ros Activationmentioning
confidence: 99%
“…Briefly, in the healthy vasculature, VSMcs display a low proliferative rate with a quiescent and contractile phenotype. However, under an external stimulus, VSMcs migrate from the medial layer into the intimal layer, accompanied by a switch to a proliferative synthetic phenotype (37). This phenotypic transformation in associated with reduced expression of contractility markers SMα-actin and SM-MHc; however, the production of inflammatory cytokines is increased (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Normal, mature and stable SMCs contain abundant muscle bers, with poor proliferation and migration ability, which are contractile phenotype. In response to vascular injury, the activated in ammatory cells, platelets and SMCs release the growth factors, especially platelet-derived growth factor (PDGF), thereby leading to a switch of SMCs from a contractile phenotype to a synthetic phenotype [48][49][50]. PDGFB is described to be one of the most potent stimulants for SMCs proliferation and migration [51].…”
Section: Discussionmentioning
confidence: 99%